Assessment of consolidation-induced VOC transport for a GML/GCL/CCL composite liner system. Issue 4 (August 2018) - Pu, Hefu; Qiu, Jinwei; Zhang, Rongjun; Zheng, Junjie
Abstract: In municipal solid waste landfills, a triple-layer composite liner consisting of a geomembrane liner (GML), a geosynthetic clay liner (GCL) and a compacted clay liner (CCL) is commonly used at the landfill bottom to isolate the leachates from surrounding environment. This paper presents a numerical investigation of the effect of liner consolidation on the transport of a volatile organic compound (VOC), trichloroethylene (TCE), through the GML/GCL/CCL composite liner system. The numerical simulations were performed using the model CST3, which is a piecewise linear numerical model for coupled consolidation and solute transport in multi-layered soil media and has been extensively validated using analytical solutions, numerical solutions and experimental results. The performed numerical simulations considered coupled consolidation and contaminant transport with representative geometry, material properties, and applied stress conditions for a GML/GCL/CCL liner system. The simulation results indicate that, depending on conditions, consolidation of the GCL and CCL can have significant impact on the transport results of TCE (i.e., TCE mass flux, cumulative TCE mass outflow, and distribution of TCE concentration within the GCL and CCL), both during the consolidation process and long after the completion of consolidation. The traditional approach for the assessment of liner performance neglects consolidation of the GCL and CCL and fails to consider the consolidation-induced transient advection and concurrent changes in material properties and, therefore, can lead to significantly different results. These differences for with and without the consolidation effects can range over several orders of magnitude. The process of consolidation-induced contaminant transport is complex and involves many variables, and therefore case-specific analysis is necessary to assess the significance of liner consolidation on VOC transport through a GML/GCL/CCL composite liner system.